Technical Note: An approach to building a Monte Carlo simulation model for a double scattering proton beam system. Issue 6 (18th April 2018) - Yuan, Jiankui; Ellis, Rodney; Machtay, Mitchell
Abstract : Purpose: The purpose of this study was to demonstrate and develop a Monte Carlo (MC) simulation model for a passive double scattering compact proton therapy system based on limited information of the mechanical components. Method: We built a virtual machine source model (VMSM) which included a detailed definition of each beam‐modifying component in the nozzle. Conceptually, it is similar to the conventional virtual analytical source model (VASM), except that the numerical machine nozzle or beamline is constructed in the VMSM, whereas in the VASM analytical parameters characterizing the energy spectrum and source fluence distribution are sought. All major beam shaping components were included in the VMSM and the model simulates interactions of the beam with a rotating range modulation wheel (RMW) combined with the beam current modulation. The RMWs, the first and second scatterer in the system were generated and tuned to reproduce measurement data as closely as possible. To validate the model, we compared the percent depth dose curves, spread out Bragg peaks (SOBPs) and lateral profiles against measured commissioning beam data. Results: The agreement of beam range between the MC calculation and measurement was within 1 mm for all beam options. The distal‐falloff length was in good agreement as well (<1 mm for the large and deep groups, <1.5 mm for the small group). Agreement to within 2.5 mm of measured SOBP widths was obtained for all MC calculations. For lateral profiles, differences were found to be less than 2 mm. Conclusions: We demonstrated that with limited geometrical information it is possible to build an acceptable source model for MC simulations of a passive double scattering compact proton therapy system. The agreement between the measurements and the MC model provides validation for use of the model for further studies of the dosimetric effects in patient treatments.